UJI FITOKIMIA DAN UJI TOKSISITAS EKSTRAK ETANOL KULIT BATANG KRATOM (Mitragyna speciosa Korth.) DENGAN METODE BRINE SHRIMP LETHALITY TEST (BSLT) - Rohadi, Imam; Erwin, Erwin; Aziz, Abdul (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Kalimantan people often use plants as traditional medicine, one of which is the Kratom plant (Mitragyna speciosa Korth.). Kratom in low doses can have a stimulant effect and cause narcotic effects at high doses, so this plant is interesting to study for its chemical compound content. The aim of this research is to determine the content of secondary metabolite compounds and the level of toxicity of the kratom stem bark ethanol extract against Artemia salina L. larvae. The methods used in this research are extraction, phytochemical tests and the Brine Shrimp Lethality Test (BSLT). The results showed that the ethanol extract of kratom stem bark contains alkaloids, triterpenoids, phenolics, flavonoids and quinones. Furthermore, the BSLT test results showed that the ethanol extract of kratom stem bark has a toxicity level of 235.15 ppm in the toxic category (LC50 < 1000 ppm). Based on these results, it can be concluded that the ethanol extract of kratom stem bark has the potential to have bioactivity because it is toxic to Artemia salina L. shrimp larvae. Keywords: Phytochemicals, Kratom, Secondary Metabolites, Toxicity.